274 Colonization of Methicillin-Resistant Staphylococcus Aureus With High-Level Resistance To Mupirocin In Korean Children. (October 2012) - Lee, JH; Kim, SJ; Lee, J; Lee, HS; Kim, SY; Sung, IK
Abstract : Increased mupirocin use has been considered as a major cause to develop mupirocin resistance among MRSA isolates. High-level mupirocin resistance (HLMR) is associated with decolonization failure, but fortunately most MRSA have showed low-level mupirocin resistance (LLMR). Recently, we became aware of markedly high prevalence of clinical isolates with HLMR among Korean children. We investigated the proportion of HLMR isolates and mupirocin use between children (less than 18 years) and adult patients. A total of 1134 MRSA (213 children and 921 adults) isolates were identified from two university hospitals in 2010–2011. Antimicrobial susceptibility testing was firstly performed by using the Vitek 2 instrument (bioMerieux, Marcy I'Etoile, France). The mupA genes were detected by polymerase chain reactions. Overall, 38% of isolates collected from children showed HLMR, whereas 3.4% showed HLMR in adults. Children revealed only one LLMR isolate (0.4%), and adult patients had 80 LLMR isolates (8.6%). This tendency was also observed, when the patients were divided into two groups under intensive care units or outpatient settings. A total of 4, 009 mupirocin prescriptions were dispensed at our institutions during 2006. Afterward, there were 4, 760, 5, 250, 6, 416, and 8, 038 prescriptions from 2007 to 2010, respectively. But, prescription rates of mupirocin did not significantly differ between children and adults. In children with MRSA isolates, the presence of previous admission, prolonged hospitalization, and mupirocin use did not contribute to mupirocin resistance. In Korean children, the rate of HLMR in the MRSA isolates was very high and it was not associated with increased mupirocin use.